Controlled Activation of TRPV1 Channels on Microglia to Boost Their Autophagy for Clearance of Alpha-Synuclein and Enhance Therapy of Parkinson's Disease - Yuan, Jiaxin (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.